2023
DOI: 10.1101/2023.03.14.532601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transposon-encoded nucleases use guide RNAs to selfishly bias their inheritance

Abstract: Insertion sequences (IS) are compact and pervasive transposable elements found in bacteria, which encode only the genes necessary for their mobilization and maintenance. IS200/IS605 elements undergo peel-and-paste transposition catalyzed by a TnpA transposase, but intriguingly, they also encode diverse, TnpB- and IscB-family proteins that are evolutionarily related to the CRISPR-associated effectors Cas12 and Cas9, respectively. Recent studies demonstrated that TnpB-family enzymes function as RNA-guided DNA en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“… 51 The limited TAM diversity of TnpBs may be explained by the co-evolution of TnpA and TnpB, as TnpA also utilizes the TAM to recognize the transposon ssDNA for excision and insertion. 1 , 2 , 6 , 43 , 52 Although it is not yet clear how, if at all, TnpB interacts with TnpA and the transposon DNA, the fact that both proteins possess the same TAM sequence is a clear constraint on the TAM diversity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 51 The limited TAM diversity of TnpBs may be explained by the co-evolution of TnpA and TnpB, as TnpA also utilizes the TAM to recognize the transposon ssDNA for excision and insertion. 1 , 2 , 6 , 43 , 52 Although it is not yet clear how, if at all, TnpB interacts with TnpA and the transposon DNA, the fact that both proteins possess the same TAM sequence is a clear constraint on the TAM diversity.…”
Section: Resultsmentioning
confidence: 99%
“…According to recent evidence, TnpB improves retention of its transposon whereby an ωRNA expressed from one transposon locus targets transposon-lacking versions of that locus in the same cell, that is, loci where the transposon has not yet inserted or those which have undergone excision. 6 Therefore, it appears that TnpB DNA cleavage serves to fix the transposon-containing locus in the population by eliminating loci that have undergone excision 1 and/or homing to un-inserted loci. 2 , 54 Under this hypothesis, the TnpB mRNA could serve as a temporally-sensitive signal of active transcription of the transposon and its continued presence in the genome and, therefore, exert negative feedback on TnpB DNA cleavage to prevent unnecessary genome instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Experimental reconstitution of IS200/IS605 elements from Geobacillus stearothermophilus showed that IscB targeted the donor joint for cleavage, allowing for retention of the transposable element in the donor strand following peel-out-paste-in transposition. 53 Type II systems have a nearly uniform gene composition and locus organization compared to the diversity of class 1 CRISPR. Nevertheless, there are three type II subtypes, of which two encompass distinct, signature genes.…”
Section: ■ Diversity Evolution and Classification Of Crispr Systemsmentioning
confidence: 99%
“…Recently, it has been shown that IscB is a guide RNA-dependent endonuclease that is potentially involved in RNA-guided homing of the respective transposons, in a manner similar to that proposed for other IS200/IS605 transposons . Experimental reconstitution of IS200/IS605 elements from Geobacillus stearothermophilus showed that IscB targeted the donor joint for cleavage, allowing for retention of the transposable element in the donor strand following peel-out-paste-in transposition …”
Section: Diversity Evolution and Classification Of Crispr Systemsmentioning
confidence: 99%